Prevalence and associated factors of Smokeless Tobacco (SLT) use among adolescents in Indonesia: GYTS 2019 data analysis - Syamsuriansyah, Syamsuriansyah; Salman, Salman; Rusmitasari, Heni; Sari, Marlynda Happy Nurmalita; Maretalinia, Maretalinia (YCAB Publisher & IAKMI SULTRA, 2022)
Background: Smokeless tobacco (SLT) use is a new trend since the banning of smoking in many public places, including among adolescents. Many people believe that SLT is a harmful reduction method compared to cigarettes. However, there are many risks of using the SLT, such as Head and neck cancer (HNC), cancer of the mouth, and coronary heart disease. Objective: This study aimed to examine the prevalence and the factors associated with SLT use among adolescents in Indonesia. Methods: This study used the cross-sectional data from the Global Youth Tobacco Survey (GYTS) Indonesia 2019. The national school was selected by proportional random sampling. Around 8,828 students were eligible for this study. Results: This study found the prevalence of SLT use was 3.25%. The bivariate test found each independent variable was significantly associated with the SLT use. However, the adjusted test found that age, smoking parent, smoking teacher, knowledge, and attitude were significantly associated with SLT use. Conclusion: The variables mostly related to SLT use come from the family and school environment. The appropriate intervention needs to be arranged to reduce the prevalence of smokers, including SLT use.